DEVELOPMENT OF PROFESSIONAL COMPETENCES IN THE TRAINING OF FUTURE PRIMARY TEACHERS (Multidisciplinary Journal of Science and Technology, 2026)
This article discusses the structure of the methodological system for developing professional competence of future primary school teachers, its content and how to implement organizational factors of development. The concept of professional competence and directions of its development are highlighted.